Occupational radiation safety studies in Nepal – a review (International Journal of Occupational Safety and Health, 2022)
Occupational radiation safety and health is the most neglected aspect in the health sector in Nepal. There has been gross negligence in occupational safety and health as a whole in Nepal. This paper is a review of previously published articles on topics of occupational radiation safety and health in Nepal. Keywords such as Nepal, occupational safety, radiation safety, radiation risk, and health were used to search for relevant articles in PUBMED and Google Scholar.A total of 15 research articles were reviewed, which dealt with different forms of occupational radiation risks and exposure, regulatory works and consequently its knowledge and awareness among the professionals. The reviewed articles are basically of 3 types: analytical or progress reports, knowledge or awareness assessment, and measurement-based research articles.The overall status of occupational radiation safety and health does not look satisfactory. Although occupational radiation safety and health is a very important issue at an individual, social and national level in any hospital, agricultural or industrial sector, it has not received much attention so far in Nepal. This is evident by the minimal number of literature available on the status of occupational radiation safety and health in Nepal. Standard work situations and criteria have to be set up and regular radiation monitoring should be done to ensure the maintenance of quality at work. In addition, workshops, seminars, symposiums, training courses, and Continuing Professional Education (CPE) programs should be organized regularly to raise the level of radiation awareness in the profession. The state agencies need to develop and update respective national laws, policy and programs for occupational radiation safety and health. There is an utmost need for extensive researches to be performed covering overall radiation health and other services of the professionals in Nepal where radiation is being used for their advantageous purposes.